Keefektifan Penggunaan Storyboard Dalam Pembuatan Film Pendek sebagai Implementasi Pembelajaran Teks Anekdot - Hasminur, Hasminur; Zulhaini, Zulhaini; Arief Rachman Hadi; Mangatur Sinaga (GERAM: Gerakan Aktif Menulis, 2022)
The research was conducted using a quasi-experimental design to determine whether the different variables work. This study aims to determine the effectiveness of using storyboards in making short films as an implementation of learning anecdotal texts in SMA/SMK/MA. This research was a quasi-experiment. The effectiveness of using storyboards in making short films as an implementation of anecdotal text learning in SMA/SMK/MA between classes that are treated using storyboards and without storyboards. Written tests and multiple-choice exams were used to develop success in this study. The experimental class was treated using storyboards in making short films of anecdotal texts, and the control class was not treated before the learning process. The research findings above show that the experimental group treatment using storyboards to make anecdotal short films is superior to the control group treatment that does not use storyboards